The Tourist Gastronomic Experience: Ties Between Young Foodies’ Motivation and Destination Development in Portugal - Andreia Antunes Moura; Maria do Rosário Mira; Ana Rita Teixeira (Tourism and Hospitality)
Gastronomic tourism has become a dynamic segment within the tourism sector, serving as a vital tool for the economic, cultural, and environmental growth of regions that emphasize culinary experiences. This study examines the motivations of young food-motivated tourists (“foodies”) and their impact on travel choices and destination development. Using a quantitative methodology, data were collected from 170 respondents (131 valid answers) in Portugal. The data were collected through the PTFoodies survey, a tool specifically designed by the authors to analyze tourist motivations and their connections to destination attributes. Principal Component Analysis (PCA) identified five key factors—endogenous products, local gastronomy, quality and innovation, authenticity and tradition, and diversity—revealing a balance between sustainability, local authenticity, and openness to innovation in tourist preferences. Additionally, correlation analysis highlighted significant relationships between motivations, such as the strong association between an interest in culinary routes and event participation and between local product appreciation and the preference for organic food. These findings contribute to both theory and practice by refining motivational theories specific to gastronomic tourism, offering insights into destination development strategies and emphasizing sustainable practices that resonate with tourists’ preferences. The study provides destination managers with actionable strategies to attract food-motivated tourists and foster sustainable community growth through gastronomic tourism.